Prohibitins in neurodegeneration and mitochondrial homeostasis - Fernandez-Abascal, Jesus; Artal-Sanz, Marta (Frontiers in Aging, 2022)
The incidence of age-related neurodegenerative disorders has risen with the increase of life expectancy. Unfortunately, the diagnosis of such disorders is in most cases only possible when the neurodegeneration status is already advanced, and symptoms are evident. Although age-related neurodegeneration is a common phenomenon in living animals, the cellular and molecular mechanisms behind remain poorly understood. Pathways leading to neurodegeneration usually diverge from a common starting point, mitochondrial stress, which can serve as a potential target for early diagnosis and treatments. Interestingly, the evolutionarily conserved mitochondrial prohibitin (PHB) complex is a key regulator of ageing and metabolism that has been associated with neurodegenerative diseases. However, its role in neurodegeneration is still not well characterized. The PHB complex shows protective or toxic effects in different genetic and physiological contexts, while mitochondrial and cellular stress promote both up and downregulation of PHB expression. With this review we aim to shed light into the complex world of PHB’s function in neurodegeneration by putting together the latest advances in neurodegeneration and mitochondrial homeostasis associated with PHB. A better understanding of the role of PHB in neurodegeneration will add knowledge to neuron deterioration during ageing and help to identify early molecular markers of mitochondrial stress. This review will deepen our understanding of age-related neurodegeneration and provide questions to be addressed, relevant to human health and to improve the life quality of the elderly.